Development of highly sensitive polysilicon nanogap withAPTES/GOx based lab-on-chip biosensor to determine low levelsof salivary glucose - Sharma Rao Balakrishnan; U. Hashim; G.R. Letchumanan; M. Kashif; A.R. Ruslinda; W.W. Liu; P. Veeradasan; R. Haarindra Prasad; K.L. Foo; P. Poopalan (Elsevier, 2024)
Volume 220